Empowering Women Entrepreneurs: Economic, Social, and Environmental Contributions to Tourism Development in South Sulawesi - Firman, Afrizal; Maichal, Maichal (Universitas Muhammadiyah Yogyakarta, 2025)
This study explores how economic, social, and environmental empowerment affects women entrepreneurs in micro-small-medium enterprises (UMKM) in the tourism sector of South Sulawesi and the resulting implications for sustainable tourism development. This study shows sustainability traits, and all hypotheses offer substantial evidence for the connection between women's attributes of sustainability empowerment and sustainable tourism. To assess the hypotheses and ascertain the reliability and validity of this study, quantitative methods of SmartPLS-SEM 4.0. tool and questionnaire surveys from 100 women entrepreneurs are employed. The findings enhance our comprehension of women's empowerment within theory and provide managerial insights for women entrepreneurs aiming to effectively engage visitors in sustainable tourism development in South Sulawesi. The research concludes the need for collaborative efforts between government and communities to empower women in tourism enterprises, fostering sustainable development. Collaboration between government and community is essential for facilitating women's empowerment in tourism enterprises, including cultural attractions and social entrepreneurship. This study highlights several limitations, focusing only on South Sulawesi with a low sample size, and proposes directions for future investigation.